Spatial Modeling of Earthquake Risk in Sulawesi and Maluku Based on Geological Factors - Rahmawati, Syarifah Desy (ESTIMASI: Journal of Statistics and Its Application, 2025)
The convergence of the Eurasian, Indo-Australian, and Pacific tectonic plates in the Sulawesi and Maluku regions results in high seismic activity, making these areas prone to frequent earthquakes. This study aims to analyze the spatial distribution of earthquake events and assess the influence of geological features such as volcanoes, active faults, and subduction zones on earthquake risk. Using the inhomogeneous Thomas cluster process, spatial modeling was conducted based on earthquake epicenter data from 2009 to 2020 with magnitudes ≥ 4.5. Each epicenter's distance to the nearest geological feature was used as a covariate. The results of the Chi-square test indicate significant spatial inhomogeneity, while the inhomogeneous K-function reveals that earthquakes tend to occur in clustered patterns. Parameter estimates show that proximity to volcanoes has the most substantial impact, increasing earthquake intensity by approximately 1.8 times for every 100 km closer to a volcano. Faults and subduction zones contribute with relative effects of 0.7 and 0.9 times, respectively. The model demonstrates good fit based on envelope simulation. Earthquake risk prediction maps identify Gorontalo, North Sulawesi, Central Sulawesi, Maluku, and North Maluku as high-risk zones. This model can serve as a valuable tool to support disaster mitigation planning and improve regional earthquake preparedness strategies.